Growth increase of Silver Pompano (Trachinotus blochii) Stimulated by Recombinant Growth Hormone (rGH) Addition on Their Commercial Feed - Wiwin Kusuma Atmaja Putra; Tengku Said Raza'i (Journal Omni-Akuatika, 2018)
The aims of the study was to determine the effect of recombinant growth hormone (rGH) on the growth of Silver pompano (Trachinotus blochii). This research was conducted using Complete Random Device) design experimentation i.e. control (non rGH), A (2 mg.kg-1), B (of 3 mg.kg-1), and C (4 mg.kg-1) of feed dry wieght (w/w) by four individual restating (each test 15 fish). Several parameter was observeb included absolute Growth, Specific Growth, feed convertion ratio, survival rate, mortality and water quality (DO, pH, temperature and salinity). The results showed that treatment C resulting an absolute growth of 19.9 g with a specific growth 0.71 g/ day). Feed convertion ratio was 5.8 while survival rate was 16.67% and Mortality reached 83.33 %. Results The analysis of water quality parameters are range DO (5.2-7.1mg L-1), salinity (25-28 ppt), pH (6.8-7.1) and temperature (30-31.2° C). Reviews These results indicate that rGH can increase the growth S. pompano fish compared to the control treatment.Keyword: recombinant Growth Hormone, Growth, Silver pompano